Differences in public and producer attitudes toward animal welfare in the red meat industries - Coleman, Grahame J.; Hemsworth, Paul H.; Hemsworth, Lauren M.; Munoz, Carolina A.; Rice, Maxine (Frontiers in Psychology, 2022)
Societal concerns dictate the need for animal welfare standards and legislation. The public and livestock producers often differ on their views of livestock welfare, and failure to meet public expectations may threaten the “social license to operate” increasing the cost of production and hampering the success of the industry. This study examined public and producer attitudes towards common practices and animal welfare issues in the Australian red meat industry, knowledge of these practices, and public and producer trust in people working the red meat industry using an Australia-wide survey of both the general public (n = 501) and red meat producers (n = 200). Public participants were recruited using a random digit dialing telephone survey (Computer-Assisted Telephone Interviewing) while the red meat producers were randomly selected within a curated database of Australian red meat producers. After controlling for gender and age, there were marked differences (p<0.01) between public and producer respondents in 20 of the 27 attitude, trust and knowledge variables studied. Producers reported more positive beliefs in the conditions provided for sheep and beef cattle during sea and land transport, the husbandry practices used in the red meat industry, and red meat attributes regarding human health, environmental impact, animal use and animal welfare. Both public and producers reported similar levels of trust in conventional and commercial media and had similar beliefs about animal rights, prevention of animal cruelty and balancing the welfare of people and animals. The results indicate a polarization between the public and livestock producers in their attitudes towards animal welfare, knowledge of husbandry practices and trust in livestock people.